The evidentiary effect of the contract particulars under the rotterdam rules - (:unkn) unknown (My University, 2012)
0

The contract particulars have crucial importance when an action is brought against the carrier. They assist to the claimants, and therefore, the Convention renders them some statutory evidentiary values. Depending on the holder of the transport document, the contract particulars in a transport document are traditionally specified as either prima facie evidence or conclusive evidence. The Rotterdam Rules follows the traditional division, but it introduces some novelties in respect of the conclusive evidence rule. This article examines that how the Convention regulates the prima facie evidence rule and the conclusive evidence rule.
Keywords: Hukuk